A sulfur–eugenol allyl ether copolymer: a material synthesized via inverse vulcanization from renewable resources and its application in Li–S batteries. (11th May 2017) - Hoefling, Alexander; Nguyen, Dan Thien; Lee, Young Joo; Song, Seung-Wan; Theato, Patrick
Abstract : Polymeric materials based on abundant elemental sulfur and renewable eugenol show enhanced cyclability as cathode materials in Li–S batteries. Abstract : The demand for eco-friendly and renewable resources has dramatically increased in scientific and technological areas including energy storage systems and production of new functional materials. Sulfur copolymers with high sulfur contents of up to 90 wt% were prepared via inverse vulcanization from environment-friendly, sustainable raw materials: cost-effective waste-product elemental sulfur and eugenol allyl ether (EAE), which is obtained from clove oil. The thermal properties and electrochemical activities of the resulting poly(S- co -EAE) materials can be tuned by controlling the EAE : S feed ratio. Employed as a cathode material in Li–S batteries, the copolymer with 90 wt% sulfur content provides good cycling stability at a capacity of ∼650 mA h g −1 and high Coulombic efficiencies (>99%) over 100 cycles.